Resilient Reformer : The Life and Thought of Martin Luther - Lull, Timothy F.; Nelson, Derek R. (Book collections on Project MUSE., 2015)
Some would argue that there is no need for yet another biography of Martin Luther. The story has been told many times, and very well at that! And yet, interest in Luther's life and thought remains high, and each generation brings its own set of questions to the task. This biography, begun by Timothy F. Lull prior to his death and capably finished by Derek R. Nelson, is marked for its fresh, winsome, and invigorating style--one undoubtedly shaped by the years that each author spent in undergraduate and seminary classrooms. In this telling, Luther is an energetic, resilient actor, driven by very human strengths and failings, always wishing to do right by his understanding of God and the witness of the Scriptures. Luther is portrayed here more as a loud tenor in a Reformation chorale than as a solo voice of dissent against church and empire, as he and his work are closely linked with his many collaborators. At times humorous, always realistic, and appropriately critical when necessary, Lull and Nelson tell the story of an amazing, unforgettable life, one that impacted our world in countless ways.